Microbial Induced Slope Surface Stabilization Using Industrial-Grade Chemicals: A Preliminary Laboratory Study. - Gowthaman, S.; Mitsuyama, S.; Nakashima, K.; Komatsu, M.; Kawasaki, S. (GEOMATE International Society., 2019)
One of the promising soil improvement techniques that have recently gained increased attention in Geotechnical and Civil Engineering is microbial induced carbonate precipitation (MICP). The MICP is mediated by ureolytic bacteria through a chain of biochemical reactions which lead to the formation of calcium carbonate cement in soil matrix and persuades the substantial bonds between the soil particles. The study presented herein focuses on surficial stabilization of slope soil (Hokkaido, Japan) by mediating industrial-grade chemicals through two different scales of preliminary laboratory investigations: small-scale columns and bench-scale slopes. Locally isolated Psychrobacillus sp. was cultivated in both industrial-grade media (beer yeast) and laboratory-grade media (NH4-YE: tris-buffer, ammonium sulfate and yeast extract), and the urease activities were compared. The results showed that the cultivation of bacteria in beer yeast resulted in higher urease activity (0.9 U/mL) compared to that in conventional laboratory media (0.4 U/mL). Also, UCS of the specimen treated using industrial-grade chemicals (urea fertilizer, beer yeast and snow melting reagent) was about two times higher than the specimen treated using conventional laboratory-grade chemicals (urea, CaCl2 and nutrient broth). The benchtop-scale test revealed that the highest surface strength (UCS of 1.02 MPa) was achieved while treating the soil by 0.5 M cementation solution at 30ºC. Sets of colorimeter measurements were undertaken on treated slope models to compare precipitation profile at different locations. These findings suggest that industrial-grade chemicals can contribute as potential candidates in MICP applications from the perspective of cost reduction.
Keywords: Microbial induced carbonate precipitation (MICP).; Industrial-grade chemicals.; Laboratory-grade chemicals.; Locally isolated ureolytic bacteria.; Cost reduction.